The market timing effect on capital structure decisions : Evidence from Nordic stock markets 2000-2018 - Li, Bob (My University, 2022)
The study examines the market timing impact on capital structure decision. The market timing theory, presented by Baker & Wurgler in 2002, as an opposition to the more static capital structure approach which were introduced previously. The market timing theory seeks to examine the role of external factors i.e., different market environments when deciding the sources of funding (debt or equity) instead of the traditional approach of assessing internal factors. The theory has been widely examined through analyses on U.K. and U.S. stock markets but the literature involving Nordic countries has been limited. Thus, the study focuses solely on Nordic (Finland, Sweden, Norway, Denmark, and Iceland) firms as the as the sample for testing the hypotheses. Literature has identified several motives behind market timing on IPO activity, taking advantage of “window of opportunity” as one of the most established explanations. Other motives identified include higher stock return and market to book opportunities in the hot market conditions. The research questions are studied first through reviewing current established theories in the capital structure field and emphasizing market timing theory. Secondly, an overview of prior literature on market timing theory associated with IPOs is presented, with an emphasis on leverage and capital structure determinants. Lastly, the empirical study is presented through a form of quantitative analysis using OLS regression models with chosen variables which emulate prior studies. The empirical part of this study explores the market timing impact on firm’s financing policy regarding the capital structure decision in the Nordic stock markets. Due to the cyclical nature in IPOs activity, the hot and cold market classifications are employed as the equity timing metric, in line with previous studies. Firms utilizing market timing in their capital structure decision regarding equity issuance i.e., hot market firms are marked by particularly strong IPO activity due to more favorable market conditions. In comparison to cold market counterparts, the empirical study did not find evidence for hot market firms issuing more primary proceeds than cold market counterparts. However, hot market companies had higher decrease in their leverage ratios over the offering year. Contrarily, cold market firms begin to expand their leverage levels at a faster rate than hot market firms after the offering have taken place, which may be an indication taking more debt as a buffer due to market uncertainty and volatility associated with cold market conditions as studies have suggested. However, the market timing effect from a long-term perspective in IPO on capital structure balancing shows very small long-term effect for the 2000-2018 sample, as the effect faded from the second year onwards after IPO had taken place. When looking at firm characteristics of firms conducting IPOs during a hot market period, the study identifies them as being characterized by smaller size measured in sales and inferior financial performance in terms of profitability compared to cold market firms
Keywords: Capital structure, Leverage, Market timing, Hot and cold markets, Initial public offerings